STRENGTHENING REGIONAL ASSET GOVERNANCE: SYNERGY AND INNOVATION IN THE IMPLEMENTATION OF E-BMD IN REJANG LEBONG REGENCY - Librial intansyari; Robinson; Fachruzzaman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to examine how synergy among asset management stakeholders supports the successful implementation of the Electronic Barang Milik Daerah (eBMD) system in Rejang Lebong Regency, and to identify innovations that enhance the accuracy, reliability, and accountability of asset information used in regional financial reporting.